Application of Earned Value Analysis Method and Earned Schedule Method to Time and Cost Control In Bank X Building Project - Dina Afrila; Egi Reksa Gumelar; Muhammad Abdu Silman; Aryati Indah Kusumastuti (CV. Syntax Corporation Indonesia, 2024)
Construction projects are activities that must be completed within limited time and resources. This research aims to identify risky activities and make control efforts to reduce the level of hazard risk in the installation of steel box girder on the bridge. This research used a mixed methods approach, combining quantitative and qualitative methods. Data were collected through surveys and interviews with 60 respondents from 35 bridge projects. The results showed that there were 29 variables of work accident risk factors, including 3 variables with moderate risk levels, 24 variables with high risk levels, and 2 variables with extreme risk levels. The highest risk factors were mobilization that caused congestion and crane overturning during girder lifting that caused operators to fall. To reduce the risk level, efforts are made to ensure all work is done correctly, conduct regular safety inspections, and ensure an effective communication system in the installation of steel box girders on the bridge. The findings can serve as a basis for policy makers to develop better OHS regulations and guidelines, as well as provide valuable information for the development of more effective safety training programs for workers in the construction sector.